Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Review - Page 904: 6


$(g\circ f)(x)=x^2-1$

Work Step by Step

Functions involved: $f(x)=x^2-2$ $g(x)=x+1$ Substitute $f(x)$ into $g(x)$: $(g\circ f)(x)=(x^2-2)+1$ Simplify: $(g\circ f)(x)=x^2-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.